2017
DOI: 10.1080/08952841.2016.1256734
|View full text |Cite
|
Sign up to set email alerts
|

Impact of demographic variables on women’s economic empowerment: An ordered probit model

Abstract: The present study aimed to empirically examine the demographic variables that determine women's economic empowerment. A sample of 500 married women between 21 and 49 years old (M = 35.49, SD = 7.66) was conveniently selected from district Multan (Pakistan). Control over economic resources was used as a proxy for women's economic empowerment. Ordered probit regression was run to assess the demographic determinants (i.e., age, education, paid job, income, and property) of economic empowerment of the least empowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The current result is likely because women who are advanced in age may command some level of respect/recognition from sociocultural perspective. Azra Batool et al (2018) also espoused that advanced age benefits the entire family in addition to affecting women's lives positively. For instance, children of empowered women tend to receive better education.…”
Section: Discussionmentioning
confidence: 99%
“…The current result is likely because women who are advanced in age may command some level of respect/recognition from sociocultural perspective. Azra Batool et al (2018) also espoused that advanced age benefits the entire family in addition to affecting women's lives positively. For instance, children of empowered women tend to receive better education.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing age of women who work as songket craftsmen has a strong enough influence on the decision to work on their own business or work in someone else's business. Batool & Jadoon (2018), Sheikh et al, (2016), and Batool et al, (2017 found the same thing where women's age had a positive and significant effect on women's empowerment. However, in contrast to the findings of Haque et al (2011), it is concluded that women's age does not have an influence on women's empowerment, especially in economic decision making and household decision-making.…”
Section: Estimation Of the Probability Of Empowering Women Working In Other's Businessesmentioning
confidence: 82%
“…Women in the 40-44 year age group showed the highest chance of making economic decisions 2.82 times compared to those in the reference age category. Batool et al (2017) and Sheikh et al(2016) state that women's age has a positive and significant effect on women's empowerment. The older you get, the better your understanding of a job will be, and you will get richer work experience.…”
Section: Determinants Of Women's Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…This statistical method is a relatively standard approach. For example, Azra Batool et al, (2018) used the same approach to explore the influence of demographic variables on economic empowerment.…”
Section: The Relationship Between Time Discounting and Adoption Intentionmentioning
confidence: 99%